Near peer teaching in general practice: option or expectation?. Issue 6 (2nd November 2019) - Alberti, Hugh; Rosenthal, Joe; Kirtchuk, Liza; Thampy, Harish; Harrison, Michael
ABSTRACT: General Practice (GP) trainees who teach medical students do so as near peers with established educational benefits for all concerned. Through teaching, GP trainees consolidate their own knowledge and skills whilst students value the experience of learning from teachers closer in age and stage. Importantly, involving GP trainees as teachers increases primary care teaching capacity and promotes GP as a potential career option for undergraduates. However, whilst junior doctors are often to be found teaching on hospital wards and in clinics, GP trainees based in primary care appear to have fewer opportunities to teach. This article encourages the promotion of near peer teaching in primary care on several levels. We make practical suggestions of potential benefit to the individual GP trainee, trainer and practice. We also discuss ways in which key stakeholders, including medical schools and those organising post-graduate primary care training programmes, may promote near peer teaching in GP. We propose that all medical students should have experience of being taught by GP trainees, and that all future general practitioners should have training and experience of teaching undergraduate medical students.